Factors Affecting Farmer's Decision to Use Fertilizer: An Event History Modelling Approach - Adhikari, Dadhi (Economic Journal of Nepal, 2011)
Despite decades of agriculture policies to promote fertilizer use in farm for improving agriculture productivity, its use in Nepal is very low. This paper analyzes the factors influencing fertilizer adoption decision by farmer using event history modelling approach. Information and credit are major variables that affect fertilizer adoption decision. The analysis found that farmers having better access to credit and having better exposure to information are more likely adopt fertilizer earlier than the other farmers. Poor fanners have less chance to have credit facility due to lack of collateral, they are less likely to use fertilizer. Key words: Agriculture policies; Farmers; Poverty reduction Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, Kathmandu Vol. 30, No.4, October-December, Issue No. 120, 2007 Page: 232-245 Uploaded date: 22 July, 2011